Comparison of Posterior and Combined Medial-lateral Surgical Approaches in the Treatment of Supracondylar Fractures of the Humerus among Children - Wutthipiriyaangkul, MD, Somboon (Journal of Southeast Asian Orthopaedics, 2022)
Purpose: The most effective surgical approach for the surgical treatment of supracondylar fractures has not yet been established. Two commonly used approaches are a posterior approach and a combined medial-lateral approach. We performed a retrospective study to compare these two treatment strategies. Methods: A total of 66 patients were selected for review. Each patient was treated by one of the two approach methods. Data including operative time, blood loss, radiological results, the range of motion of the elbow, Flynn’s criteria, and operative complications were collected. Results: Thirty-two patients were treated with a posterior approach, and the rest (34) were treated with a combined medial-lateral approach. A posterior approach was associated with a significantly shorter operative time. There were no significant differences in blood loss, radiological results, the range of motion of the elbow, Flynn’s criteria, and complications between the two groups. Conclusion: The posterior approach technique was as effective as the combined medial-lateral approach in the treatment of supracondylar fractures, but provided shorter operative times.